Facade Lighting of Historical Buildings and Galata Tower Application - Demiroz, Yasin; Acarkan, Bora (IEEE, 2016)
Throughout history, people need natural or artificial lighting in the regions where they live when they cant use daylight After the fire had discovered, they satisfy these needs with artificial lighting elements. People illuminate the facades of buildings and special regions with various technology since ancient times. Facade lighting with modern technology can increase originality of the structure; with the wrong application structure features, and historic value of the structure can greatly damaged. Therefore, determination of architectural lighting criterias when making design and application and to make right choices from begining of the project to the end of application is of very important. In this study; principals about to lighting desing of the historical structures, the advantages of using LED lighting fixtures at historical buildings and as a sample historical building Galata Tower lighting design examined and cost analysis were applied.
Keywords: Engineering